ANALYSIS OF FACTORS INFLUENCING STUDENTS' DECISIONS IN CHOOSING PRIVATE COLLEGE AT MUHAMMADIYAH UNIVERSITY OF NORTH SUMATRA - Nur Fadillah; Endang Sulistya Rini; Syafrizal Helmi Situmorang (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Education is a measure of the success of a nation. So that education is a very important factor that must be the center of attention in its development. Muhammadiyah University of North Sumatra has 43 study programs to fulfill market demand so that prospective new students have many choices to choose which study program they want. But in reality the number of study programs does not match the number of students. So this situation needs to be investigated further. The purpose of this study was to determine the factors that influence student decisions in selecting private universities at Muhammadiyah University, North Sumatra. This research is classified as associative research (relationship). This is research that aims to determine the relationship between two or more variables. The approach used is a quantitative approach, it is said to be a quantitative approach because the research data used is in the form of numbers or qualitative data that is calculated. The population in this study were students at the Muhammadiyah University of North Sumatra Stambuk 2022/2023, totaling 4771 people. The sample technique used in this study was using Proportionate Random Sampling. The amount of the sample is obtained by using features sample size calculator through website www.raosoft.com until obtained jthe number of samples in this study numbered 356 people. The results of the research are that social media has a positive effect on student decisions in choosing a college. Campus reputation has a positive effect on student decisions in choosing a college. The cost of education has a positive effect on student decisions in choosing a college. Future job prospects have a positive effect on student decisions in choosing a college. Social media, campus reputation, tuition fees and future job prospects all have a positive influence on students' decisions to choose a college. The results of the determination test obtained the value of R2 of 0.610 or 61%. This explains that around 61% of student decision variables can be explained by social media variables, campus reputation, tuition fees and future job prospects and the remaining 39% is explained by other variables not examined in this study.